Humanitarian Response to Electoral Violence in Nigeria – Focus On 2011 General Election - Segun Moses Ayodele, (Advances in Humanities and Contemporary Studies, 2023)
The 2011 election is infamously hailed as the most brutal and violent election in Nigeria’s history. Scores were killed; more were displaced from their places of residence, and; most were deprived of the basic necessities of subsistence. The way and manner that the government handled or tackled the humanitarian issue of the 2011 electoral violence have not been adequately understood. Consequently, underpinned by the social inclusion and stakeholders’ theories, this paper sets out to ascertain the humanitarian role the government has played in addressing those affected by the electoral violence of 2011. The study thus interrogates the major stakeholder in the management of the largest internal displacement camp in Nigeria as a result of the 2011 elections. Hence, the study relies on a limited extent on primary sources of data and heavily on secondary sources of data for analysis. This study reveals that the measures being utilized by the Nigerian government in handling the humanitarian needs of the affected population, most especially internally displaced persons as a result of the aftermath of the 2011 election violence has been on an ad-hoc basis with no solid or structured modus operandi. As an illustration, some lessons learnt by the Kenyan government in addressing some of the humanitarian needs of the affected population were made reference to. In essence, this paper advocates that the government of Nigeria ensure strict, decisive and clear-cut policies on IDPs management in order to avoid ambiguity in boundaries and in the roles of agencies managing internally displaced persons.